Effect of Xylene and Tetrahydrofuran Solvent Type on Polystyrene Layer Thickness With Spin Coating Method - Eka Rahmawati; Fadli Robiandi; Lalu A Didik; Susi Rahayu; Djoko H Santjojo; Setyawan P Sakti; Masruroh Masruroh (Natural B, Journal of Health and Environmental Sciences, 2014)
Surface modification of QCM by applying polystyrene (Ps) as a coating layer has been investigated. The PS layer was coated onto QCM sensor by using spin coating method. Polystyrene was dissolved in two different solvents i.e., xylene and Tetrahydrofuran (THF) with various concentration i,e 1%, 2%, 3%, 4%, 5% and the velocity angular of spin coater were 1500 rpm, 2000 rpm, 2500 rpm, 3000 rpm, 3500 rpm, dan 4000 rpm. The results show that different solvent result in the difference of thickness of polystyrene coating layer. By calculation with the Sauerbrey equation, the thickness of Ps layer using xylene solvent show 0.1 µm, 0.28 µm, 0.35 µm, 0.59 µm, and 0.81 µm. While by using THF, the thickness of each Ps layer are 0.15 µm, 0.43 µm, 0.84 µm, 0.97 µm, 1.28 µm. On the other hand, by applying different velocity of spin coater, the thickness of polystyrene with xylene are 0.486 µm, 0.445 µm, 0.432 µm, 0.350 µm, 0.320 µm, 0,290 µm, respectively. Moreover, the thickness of PS layer by using THF show 1.05 µm, 0.93 µm, 0.87 µm, 0.84 µm, 0.67 µm, 0.52 µm. Vapor pressure of each solvent is considered as the main property of solvent which influence the thickness of coating. The vapor pressure of THF (143 mmHg) is higher than the vapor pressure of xylene (72 mmHg), the thickness Ps layer with THF is thicker than that of by xylene solvents.